Development of a standardized curriculum integrating the child protection specialty in pediatrics and obstetrics and gynecology - Tan, Merle P. (2006)
Child abuse is and emerging silent epidemic in our country. This problem has been present for along time but only being recognized recently due to the awareness of our society that this is indeed a disease that we need to confront. It is a complex, multifactor problem that requires a multifactor solution in a multidisciplinary approach of continuum care. This implies teamwork among parents and family members, pediatricians, obstetricians-gynecologists, social workers, the police force, and even lawyers. This study was conducted in The Child Protection Unit-Network, an umbrella organization of all Child Protection Unit (CPUs) in the Philippines. There are 19 CPUs all over the country with 52 individual members composed of Pediatricians and Obstetricians. Actual fieldwork for the study took place at the Child Protection Unit of The Philippine General Hospital (CPU-PGH), the only body that conducts training for child protection specialty. This study used a research and development design done in two phases. The first phase consisted of a focus group discussion with the graduates and faculty members of the existing program. The discussion focused on the determination of basic competencies, appropriate subject matter, teaching-learning activities and evaluation of achievement. The participants were also asked to give their comments on the existing program with respect to their personal experiences as trainees. Nine graduates of the existing program participated in the focus group discussions. Based on these outputs, the researcher redesigned the existing curriculum and presented it anew. The second phase used the Delphi technique where experts in the field of child protection in the country were asked to enumerate important topics to be integrated in the standardized curriculum. There were six faculty members (5 pediatricians and 1 lawyer) and 1 alumni graduate who contributed in the Delphi technique. The content experts validated the basic competencies that must be included in the program through the Delphi technique. The researcher then formulated general and specific objectives and matched these with the topics enumerated, as well as the strategies to be used for the program. The revised curriculum design included vertically and horizontally integrated sets of subject matter, makes use of modular didactics, and practical clinical teaching-learning activities of the program. An instructional design matrix was formulated for each module and this was then submitted to the content experts for validation. Faculty members agreed on the revision that subject in child abuse be presented in modular instruction. Several topics were included in the modules such as law pertaining to child abuse, testifying in court, shaken baby syndrome, documentation and collection of evidence, child death review, and module on care for the carers. The training program was designed to specifically address the need for a standardized curriculum for child protection specialty in the Philippines. The new curriculum is designed to use modular instruction, since the trainees are all adult learners and with background in medicine. The standardized curriculum in child protection specialty is recommended for all CPUs in other regions of our country.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Pediatrics -- Curricula; Child abuse -- Prevention